Water Splitting and Transport of Ions in Electromembrane System with Bilayer Ion-Exchange Membrane - Stanislav Melnikov; Denis Bondarev; Elena Nosova; Ekaterina Melnikova; Victor Zabolotskiy (Membranes, 2020)
Bilayer ion-exchange membranes are mainly used for separating single and multiply charged ions. It is well known that in membranes in which the layers have different charges of the ionogenic groups of the matrix, the limiting current decreases, and the water splitting reaction accelerates in comparison with monolayer (isotropic) ion-exchange membranes. We study samples of bilayer ion-exchange membranes with very thin cation-exchange layers deposited on an anion-exchange membrane-substrate in this work. It was revealed that in bilayer membranes, the limiting current’s value is determined by the properties of a thin surface film (modifying layer). A linear regularity of the dependence of the non-equilibrium effective rate constant of the water-splitting reaction on the resistance of the bipolar region, which is valid for both bilayer and bipolar membranes, has been revealed. It is shown that the introduction of the catalyst significantly reduces the water-splitting voltage, but reduces the selectivity of the membrane. It is possible to regulate the fluxes of salt ions and water splitting products (hydrogen and hydroxyl ions) by changing the current density. Such an ability makes it possible to conduct a controlled process of desalting electrolytes with simultaneous pH adjustment.